Retrospective study on socio-demographic factors responsible for acceptance of IUCD among postpartum women - Sable, Pavan; Bagul, Rajendra; Singh, Alokkumar (International Journal of Research in Medical Sciences, 2019)
Background: Despite the availability of modern and scientific measures, unacceptably high numbers of maternal deaths still occur in developing countries. Spacing methods of family planning may avoid maternal and infant deaths. The Government of India launched postpartum IUCD (PPIUCD) services in the year 2000; although acceptance of Postpartum IUCD is a real concern. Methods: The retrospective study was conducted in rural government hospital in Maharashtra during 2016 - 2017. We analyzed sociodemographic variables and acceptance of Postpartum IUCD among postpartum women. The sample size was 595 (N=595). The sociodemographic factors studied included age, type of delivery, sex of newborn, socioeconomic status, educational status, etc. Results: The total postpartum women included in the study was 595, out of which, 202 (34%) accepted for postpartum IUCD whereas 393 (66%) rejected for the same. The most common age group was 20-25 years (65%), followed by age group 25-30 years (30%). Primipara was the comment group (45%) and normal vaginal delivery was common (95%). The educational status of both, the postpartum women and their husband, showed statistically significant association with acceptance of postpartum IUCD (p<0.05). Conclusions: The acceptance Postpartum IUCD was low (34%). The women’s and their husband’s educational status is an important factor in acceptance of Postpartum IUCD (p<0.05). Due attention should be given to enhancing educational level of women, also effective counselling both for pregnant woman and her husband during ANC is required.